Breast cancer risk factors assessment and BRCA-associated breast cancer evaluation in mammographic screening in India - S. K. Ternovoy; S. Matkhev; A. E. Solopova; K. A. Lesko; A. B. Abduraimov (ABV-press, 2014)
Present article evaluate the influence of leading risk factors established for breast cancer (BC) on the mammography screening efficiency. 26 912 women underwent mammography screening in 2001−2010.The direct impact of BC risk factor number on the disease stage was revealed. Diagnostic effectiveness of screening mammography decreased in patient groups with high mammographic density. The importance of control of patient groups with BC risk factors and reasonability of mam- mographic density evaluation is described.The occurrence of BRCA1/2 mutations was revealed in patients with BC identified by mammography screening. The relationship between the presence of advanced and metastatic BC and the BRCA1/2 mutations was determined.